Hubungan Pengetahuan dan Sikap dengan Tindakan Siswa terhadap Perilaku Hidup Bersih dan Sehat di SMK Negeri 2 Depok - Rochmatul Cholil (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2022)
The degree of health of children at this time still cannot be said to be good because there are still many health problems, especially in adolescents. Clean and healthy living behavior is a manifestation of the reality of human life by applying the principles of the learning process, so that this healthy living behavior will occur because of the learning process that they get every day, both in the school environment, family and in the community. The type of research conducted is a descriptive analytic survey with a cross sectional research design, namely to determine the relationship between knowledge and attitudes with student actions on clean and healthy living behavior in SMK Negeri 2 Depok. Keywords: Clean and healthy living behavior, Adolescents, Knowledge and Attitudes.